Active Sites Determination of Enzyme 1-aminocyclopropane-1-carboxylic acid synthase 2 (ACS2) of Capsicum chinense using Modeling and In Silico Docking - Pahlevi, Muhammad Rizza; Widhianata, Hani; Puspaningsih, Eunike Sri; Lestari, Juniarti Wulan; Sudibya, Eka; Suwasono, Prayitno Ribut; Habiburrahman , Novan (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2024)
The growth of Chili pepper (Capsicum chinense Jacquin.) is affected by biotic and abiotic stresses. Abiotic stress such as waterlogging increases the expression of ACS (1-aminocyclopropane-1-carboxylic acid synthase) enzyme. This enzyme plays a great role in the process of ethylene biosynthesis and encoded by multiple genes. Waterlogging causes hypoxia condition. One of ACS enzymes that responds to hypoxia condition is ACS2. The different respond to hypoxia stress among plant was assumed to be caused by a different structure of the ACS2 enzyme. This study aimed to identify and confirm the active site of Capsicum chinense Jacquin ACS2  using modeling and in silico docking. The result of the three-dimensional (3D) structure modeling showed 91% similarity of Capsicum chinense Jacquin ACS2 with the structure of the tomato (Solanum lycopersicum L.). The Capsicum chinense ACS2 confirmed five active sites that bind to the substrates asparagin396B, valine397B, thyrosine152B, threonine128B, and thyrosine92A.